The Role of Conventional Myelography in the Diagnosis and Treatment of Degenerative Spine Diseases in Low-Income Communities: a Prospective Study - Kitya, David; Punchak, Maria; Bajunirwe, Francis (World neurosurgery, 2017)
ACCEPTED MANUS Introduction: Chronic back pain is a common problem and imaging is crucial for effective diagnosis and treatment. In low-resource settings conventional myelography is a cheap alternative to MRI and CT. This study was conducted to re-examine the diagnostic reliability, effectiveness for surgical decision making and safety of conventional myelography. Methods: The study was conducted at Tenwek Mission Hospital during June 2009 and March 2010. New patients who presented with features of radiculopathy and/or myelopathy were eligible. Standard anteroposterior views were taken; oblique views were obtained from patients with radiculopathy. Cervical and lumbosacral myelography was performed using iohexal contrast. Patients were observed for complications. Those with surgically remediable lesions underwent operation. Patients were monitored for symptom improvement and complication post-operatively. Results: Fifty-one (51) patients underwent diagnostic myelography and 39 (77.8%) were positive. Lesions at levels L4/5 23 (59.0%) were the most common. Of patients with cervical lesions, 11 (73.3%) had a positive myelography compared to 28 (77.8%) of patients with lumbosacral lesions. Patients presenting with claudication were more likely to have a positive myelography, compared to those with other symptoms. There were 16 (41.0%) patients with partial spinal canal block, 6 (15.4%) with total block and 17(43.6%) with recess compression. Thirty-eight (38) patients had surgery and recess decompression was the most common procedure (n=24, 63.2%). Following surgery, symptoms due to degenerative disk disease improved in the majority of patients. Conclusions: Conventional myelography is a reliable and safe diagnostic test. Appropriate and sound surgical decisions can be made following conventional myelography tests.
Keywords: Myelography; Myelopathy; Radiculopathy; Iohexal; Claudication; Canal and recess stenosis